ZCCHC3 modulates TLR3-mediated signaling by promoting recruitment of TRIF to TLR3. (5th March 2020) - Zang, Ru; Lian, Huan; Zhong, Xuan; Yang, Qing; Shu, Hong-Bing
Abstract: Toll-like receptor 3 (TLR3)-mediated signaling is important for host defense against RNA virus. Upon viral RNA stimulation, toll and interleukin-1 receptor domain-containing adaptor inducing IFN-β (TRIF) is recruited to TLR3 and then undergoes oligomerization, which is required for the recruitment of downstream molecules to transmit signals. Here, we identified zinc finger CCHC-type containing 3 (ZCCHC3) as a positive regulator of TLR3-mediated signaling. Overexpression of ZCCHC3 promoted transcription of downstream antiviral genes stimulated by the synthetic TLR3 ligand poly(I:C). ZCCHC3-deficiency markedly inhibited TLR3- but not TLR4-mediated induction of type I interferons (IFNs) and proinflammatory cytokines. Zcchc3 −/− mice were more resistant to poly(I:C)- but not lipopolysaccharide-induced inflammatory death. Mechanistically, ZCCHC3 promoted recruitment of TRIF to TLR3 after poly(I:C) stimulation. Our findings reveal that ZCCHC3 plays an important role in TLR3-mediated innate immune response by promoting the recruitment of TRIF to TLR3 after ligand stimulation. Graphical Abstract: